Achievement appraisals, emotions and socio-cognitive processes: How they interplay in collaborative problem-solving?. (June 2020) - Avry, Sunny; Chanel, Guillaume; Bétrancourt, Mireille; Molinari, Gaëlle
Abstract: The role of emotions in (computer-supported) collaborative learning has become an important research topic. However, research has mainly focused on the relationships between emotions and socio-emotional processes. Despite an extensive literature on the role of emotions in cognitive processes, socio-cognitive processes have been scarcely explored at this point. This article aims to investigate, using control-value theory (Pekrun, 2006) as a frame of reference, how task-achievement appraisals impact both self-experienced emotions and the perception of socio-cognitive processes. An experimental study involving 28 pairs of participants playing a collaborative problem-solving computer puzzle game was carried out. Depending on the experimental conditions, participants received different false feedback about group task mastery and ranking aiming at skewing in different ways how they appraised task achievement. At the end of the task, they reported self and partner's emotions as well as their perception of their socio-cognitive exchanges. The results indicate that 1) participants experienced a large variety of achievement emotions and some of them appear more closely related to specific task-achievement appraisals, 2) achievement emotions do not mediate the relationship between task-achievement appraisals and the perception of socio-cognitive processes, 3) the level of self-experienced activation as well as the perception of activation in the partner mediate the relationship between task-achievement appraisals and the perception of socio-cognitive processes and could be used as a heuristic of socio-cognitive collaborative involvement by problem solvers, 4) partner's emotions such as gratitude appear to increase the perception of socio-cognitive processes through the reinforcement of group mastery goal. Highlights: People experience a variety of emotions in collaborative problem-solving. Some of them appear strongly related to task-achievement appraisals. Subjective feelings of achievement emotions do not mediate the perception of socio-cognitive processes. Arousal could serve as a heuristic of socio-cognitive involvement. Partner's social emotions such as gratitude could promote group mastery goal.